UPAYA PENINGKATAN KESEHATAN SEKSUAL DAN MENTAL MELALUI PENDIDIKAN KESEHATAN DI SMKN 7 SURAKARTA - Utomo, Endrat Kartiko; Soleman, Sitti Rahma; Widyastuti, Agung; Ulkhasanan, Muzaroah Ermawati (Jurnal Pengabdian Kepada Masyarakat Citra Delima, 2023)
Adolescence is a period filled with curiosity in all aspects, including sexual and mental problems. School is a place to transform values and knowledge. The existence of schools must be able to design and create a smart and moral generation. So, to realize this, it is necessary to take preventive action and increase the awareness of SMKN 7 Surakarta students about mental and sexual health to avoid deviations during adolescence. Health education was attended by 54 students. The average knowledge before being given health education is in the moderate category (46.2%), after health education has increased with an average knowledge of good (51.9). Providing health education is very necessary to be carried out on an ongoing basis so that students are always exposed to information about sexual and mental health.